Erosividade e densidade da chuva no município Palestina do Pará, Pará, Brasil - COSTA, Valkiria Andrade (2023)
Rainfall erosivity is one of the main parameters of the Universal Soil Loss Equation (USLE), which has been used to predict the amount of soil loss by water for 50 years. Investigating spatial trends in rainfall erosivity is important for soil and water conservation planning. Rain erosivity (the R factors) in many regions is expected to change due to changes in rainfall patterns related to rainfall intensity, frequency and spatial distribution of storm events that can occur with climate change. In the Amazon, studies of this nature are few, however, of great relevance, considering that most existing soils in the region have low natural fertility and are subject to high annual rainfall, conditions that favor soil erosion and impoverishment. bigger and bigger. The objective of this study is to investigate the spatial variations and density of rainfall erosivity to improve our understanding of the evolution of rainfall erosivity in the municipality of Palestina do Pará. First, we calculated rainfall erosivity in 3 seasons for 1991-2021 using precipitation data from the National Institute of Meteorology database. Second, we examined the spatial variability of rainfall erosivity, erosivity density and basic statistics for the municipality studied. The results provide insights into the evolution of rainfall erosivity and the effects of small-scale climate circulation on rainfall erosivity.